Synthesis, Antibacterial, and Antifungal Activities of 3-(4,5-Diphenyl-1H-Imidazol-2-yl)-1H-Indole Derivatives - Nirwan, N.; Pareek, C.; Chohadia, A. K.; Verma, K. K. (Journal of Scientific Research, 2023)
Indolylimidazole ring-containing natural and synthesized compounds have shown vast biological activities. These indolylimidazole compounds contain both indole and imidazole rings. The indolylimidazole structure resembling compounds 1a-1d and 2a-2d were synthesized by a green and efficient one-pot four components condensation of indole-3-carbaldehyde, benzil, ammonium-acetate, and substituted amines under microwave irradiation using Amberlyst A-15 as a recyclable catalyst. The structures of synthesized compounds were characterized by FTIR, 1H NMR, and Mass spectrometric studies. These compounds' antibacterial and antifungal activities were screened and compared with the standard drug. The compound 1c was found to be the most active derivative in these compounds, with a minimum inhibitory concentration in the range of 09.9 to 12.5 μg/mL. Compound 1d also showed potent activity against Candida albicans. The sensitivity order of compounds was found 1a<1b<1c>1d against Staphylococcus aureus, Staphylococcus epidermidis, and Escherichia coli and 1a<1b<1c<1d for C. albicans. Compound 2a showed good antimicrobial activity against E. coli and C. albicans.